An analysis of digital food advertising strategies employed by restaurant food operators in Malaysia / Maisarah Addini Abdul Rashid and Noor Baiti Mohd Borhan - Abdul Rashid, Maisarah Addini; Mohd Borhan, Noor Baiti (2021)
Online advertising has been widely used by restaurateurs since early 1990s to market and promote their food and services. Studies reported that the most commonly used online marketing by restaurants is website, including social media. Several advantages (i.e. unlimited access of information by the customers, interactive features and cost effective) were discovered in online marketing by incorporating digital advertising to promote the restaurant’s food and services. However, the types of digital advertising and their roles to promote the food and services offered at food premises remained questionable. Moreover, several studies heavily focus on the effectiveness of online marketing and digital from customer viewpoint rather than trying to understand the message behind every information and details utilised in the restaurant’s website. This study, within the descriptive research design, aims to identify various digital food advertising strategies, and determine their roles employed by the casual dining restaurateurs in Malaysia to promote their services. Seven casual dining restaurants (i.e. Malaysia owned) were approached and only two have agreed to participate in this study. Content analysis was performed on relevant text descriptors and photographs that are available in the two casual dining restaurants’ official websites. Results showed that there are three advertising strategies utilized by the websites which are information quality, food quality and restaurant quality. Behind each of the strategies there are seven element that helped to define the advertising strategies which are menu description, restaurant reviews, food presentation, variation of menu, service offered, restaurant representatives and environment. The restaurants website was observed and analysed to find out the digital marketing strategies employed by the restaurateur in promoting their products. In addition, the roles and the utilization of these marketing strategies is further discussed and found to be able to tackle the business potential consumers. This study concludes that a marketing strategy perform a huge role in positioning the product in the consumer’s mind and inform the consumers about the restaurant product and service values.